Physical development and pulmonary function in children and adolescents treated at two cystic fibrosis treatment centres in Poland - Umławska, Wioleta; Rams, Monika (Archives of Medical Science, 2009)
Introduction: Delayed physical development, delayed puberty and malnutrition are common in children suffering from cystic fibrosis Material and methods: Physical development and respiratory function were assessed in 33 children and adolescents with cystic fibrosis treated at two cystic fibrosis treatment centres in Poland. Results: Mean body height and body weight were significantly lower in the study group than in the reference population. Eightteen percent of the patients had severe developmental problems, and had body heights that were more than two standard deviations below the mean for the reference population. Over 60% of the patients were malnourished, and a third of these were severely malnourished. Mean leg length was considerably lower in the study group than in the reference population. The children with cystic fibrosis had infantile body proportions. Chest depth was higher and chest width was lower in the study group than in the reference population. Predicted FVC, predicted FEV1 and predicted FEF25-75 were lower in the study group than in the reference population. There was a strong positive correlation between nutritional status and predicted FEV1. On the other hand, there was no clear correlation between the type of CFTR gene mutation or infection caused by Pseudomonas aeruginosa and predicted FEV1. Conclusions: A full-scale study is underway to determine the effect of the type of CFTR gene mutation and infection caused by P. aeruginosa on pulmonary function in children with cystic fibrosis treated at specialized care facilities in Poland.